Tvorba účelové mapy krasového reliéfu - Josefov - Staněk, Boleslav (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Tato bakalářská práce je zaměřena na tvorbu účelové mapy v oblasti krasového reliéfu. Konkrétně se jedná o geodetické zaměření terénního reliéfu v oblasti vývěru Jedovnického potoka. Tato lokalita se nachází zhruba ve střední části Moravského krasu. Tato práce popisuje celkový proces tvorby účelové mapy.

This thesis is focused on creating special-purpose maps of karst relief. Specifically, the geodetic terrain relief in the area of seepage Jedovnický stream. This site is located roughly in the middle part of the Moravian Karst. As part of this work are assessed height and positional conditions in the locality. This thesis describes the overall process of creating special-purpose maps.
Thematical map of carst surface - the colony of Josefov
Keywords: účelová mapa; tachymetrie; polygonový pořad; bodové pole; polární metoda; vrstevnice; Thematical map; tacheometry; polygonal travel; point area; polar method; contour line